Integrating remote sensing methods during controlled exposure experiments to quantify group responses of dolphins to navy sonar. (January 2022) - Durban, J.W.; Southall, B.L.; Calambokidis, J.; Casey, C.; Fearnbach, H.; Joyce, T.W.; Fahlbusch, J.A.; Oudejans, M.G.; Fregosi, S.; Friedlaender, A.S.; Kellar, N.M.; Visser, F.
Abstract: Human noise can be harmful to sound-centric marine mammals. Significant research has focused on characterizing behavioral responses of protected cetacean species to navy mid-frequency active sonar (MFAS). Controlled exposure experiments (CEE) using animal-borne tags have proved valuable, but smaller dolphins are not amenable to tagging and groups of interacting individuals are more relevant behavioral units for these social species. To fill key data gaps on group responses of social delphinids that are exposed to navy MFAS in large numbers, we describe novel approaches for the coordinated collection and integrated analysis of multiple remotely-sensed datasets during CEEs. This involves real-time coordination of a sonar source, shore-based group tracking, aerial photogrammetry to measure fine-scale movements and passive acoustics to quantify vocal activity. Using an example CEE involving long-beaked common dolphins ( Delphinus delphis bairdii ), we demonstrate how resultant quantitative metrics can be used to estimate behavioral changes and noise exposure-response relationships. Highlights: Mid-frequency navy sonar can be harmful to sound-centric marine mammals. Exposure experiments with tags can measure behavioral responses of larger cetaceans. Abundant dolphins are too small to tag and likely respond as social groups. We collect remotely-sensed data during experiments to quantify dolphin group responses. Models estimate behavioral state changes and exposure-response relationships.